2019
DOI: 10.2147/ijn.s217974
|View full text |Cite
|
Sign up to set email alerts
|

<p>Tumor ablation using novel photothermal Na<sub>x</sub>WO<sub>3</sub> nanoparticles against breast cancer osteolytic bone metastasis</p>

Abstract: BackgroundsProfiting from the development of nanomaterials, photothermal therapy (PTT) has been discovered as efficient tumor ablation strategy for breast cancer.Materials and methodsNovel oxygen vacancy-rich tungsten bronze nanoparticles (NaxWO3) were synthesized through a simple pyrogenic decomposition process. TEM, XRD, UV-vis-NIR, photothermal conversion ability, and photothermal stability were performed. The viabilities of 293T and 4T1 cells after treating with 200 μg/mL NaxWO3 nanoparticles for 24 or 48 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 38 publications
0
9
0
1
Order By: Relevance
“…At the same time, metal nanoparticles, such as the classical platinum nanoparticles, could display enhanced accumulation at cancer-bearing bone lesions and inhibit the growth of bone cancer via PTT under an 808 nm NIR laser irradiation 48 , 50 . Jie et al reported a novel kind of oxygen vacancy-rich tungsten bronze nanoparticle (Na x WO 3 ) against breast cancer osteolytic bone metastasis, which acts via the desirable photothermal effect under NIR laser irradiation 51 . This treatment strategy could also inhibit the osteoclastic RANKL and Sclerostin expression from tumor cells, thus further attenuating downstream osteoclastogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, metal nanoparticles, such as the classical platinum nanoparticles, could display enhanced accumulation at cancer-bearing bone lesions and inhibit the growth of bone cancer via PTT under an 808 nm NIR laser irradiation 48 , 50 . Jie et al reported a novel kind of oxygen vacancy-rich tungsten bronze nanoparticle (Na x WO 3 ) against breast cancer osteolytic bone metastasis, which acts via the desirable photothermal effect under NIR laser irradiation 51 . This treatment strategy could also inhibit the osteoclastic RANKL and Sclerostin expression from tumor cells, thus further attenuating downstream osteoclastogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…These nanoparticles could increase their temperature from 25.8 °C to 41.8 °C in 5 m under the irradiation of 980 nm laser. PTT using these nanoparticles could both eliminate the subcutaneous and intratibial tumors caused by the injection of murine breast cancer (4T1) cells [ 297 ]. In addition, the hydrogenated TiO 2 coating with hierarchical micro/nano-topographies was fabricated by induction suspension plasma spraying.…”
Section: Application Of Ptt In Bone Cancermentioning
confidence: 99%
“…The cytotoxicity of the particles against breast cancer cells appeared in dose-dependence in vitro . In breast cancer models, Na x WO 3 + PTT group had the most effective inhibition of tumor and bone destruction (Jie et al., 2019 ). Except for organic photothermal materials, noble metal and inorganic materials both have nonnegligible cytotoxicity, low biodegradability and low biocompatibility.…”
Section: Therapeutic Agentsmentioning
confidence: 99%
“…BP may cause mandibular osteonecrosis and impair renal function (Sun, Han, et al., 2016 ). Denosumab was reported to increase the risk of pancreatitis and endocarditis, erysipelas, and infectious arthritis (Jie et al., 2019 ). Some newly developed drugs have not been used clinically due to their hydrophobicity, short half-life, and other disadvantages (Chew & Danti, 2017 ).…”
Section: Introductionmentioning
confidence: 99%